Faunal diversity assessment of terrestrial vertebrates in forest ecosystems (Zoological Records and Reviews, 2022)
Tropical and subtropical forest ecosystems harbour the majority of Earth's terrestrial vertebrate diversity, yetcomprehensive multi-taxon faunal assessments combining mammals, birds, reptiles, and amphibians remain rare due tothe logistical and expertise demands of simultaneously surveying four vertebrate classes. This study presents asystematic faunal diversity assessment of terrestrial vertebrates across three forest ecosystem types -- tropical moistdeciduous, dry deciduous, and semi-evergreen forest -- in the central Eastern Ghats of India (Andhra Pradesh andOdisha), using standardised camera trapping, transect surveys, acoustic monitoring, and pitfall trapping protocols at 36survey sites over a two-year period (2019-2021). A total of 428 terrestrial vertebrate species are documented across thefour classes: 84 mammals, 186 birds, 98 reptiles, and 60 amphibians. Species richness is consistently highest insemi-evergreen forest (mean 124.4 species per site) and lowest in degraded dry deciduous forest (mean 64.8 speciesper site). Forest patch area, distance from the forest edge, and canopy cover are the three strongest predictors ofvertebrate species richness across all classes. Camera trap data document the presence of four large mammal speciesof conservation significance -- tiger (Panthera tigris), leopard (Panthera pardus), gaur (Bos gaurus), and Indian elephant(Elephas maximus) -- at multiple sites. Forty-six species are assessed as IUCN Threatened. Deforestation, habitatfragmentation, and human-wildlife conflict are identified as the dominant threats. An integrated conservationmanagement framework for Eastern Ghats forest vertebrates is proposed.
Keywords: conservation; amphibians; reptiles; birds; mammals; camera trapping; faunal diversity; forest ecosystems; Eastern Ghats; terrestrial vertebrates